The Value of 99mTc-Methylene Diphosphonate Single-Photon Emission Computed Tomography/Computed Tomography in Detecting Atraumatic Costal Cartilage Fracture in Malignant Tumor Patients - Li, Wei; Zhang, Linqi; Li, Wen; Zhang, Rusen (Frontiers in Oncology, 2020)
Objectives: To assess the clinical significance and single-photon emission computed tomography/computed tomography (SPECT/CT) features of atraumatic costal cartilage fracture (CCF) in patients with malignant tumors. Methods: This was a retrospective review of 38 tumor patients with atraumatic CCF referred to SPECT/CT, who were served as the study group (SG). The features of SPECT/CT of atraumatic CCF were assessed. Another 100 tumor patients who underwent chest SPECT/CT and did not have CCF were randomly selected as the control group (CG). In all patients (SG + CG), the diagnostic powers in the detection of atraumatic CCF were computed among CT, SPECT, and SPECT/CT. The final diagnosis was based on pathological findings and radiologic follow-up of at least 1 year. Results: On SPECT/CT images of atraumatic CCF in the SG, fracture lines, irregular calcification, deformation, and swelling were, respectively, noted in 26.3, 47.4, 34.2, and 18.4% of lesions; low, moderate, and high uptake were, respectively, noted in 13.2, 52.6, and 34.2% of lesions. In all patients (SG + CG), the diagnostic powers in the detection of atraumatic CCF of CT, SPECT, and SPECT/CT were as follows: sensitivity 63.2, 100.0, and 92.1%; specificity 86.0, 81.0, and 94.0%; negative predictive value 86.0, 100.0, and 96.9%; positive predictive value 63.1, 66.7, and 85.4%; and area under the curve value 0.746, 0.905, and 0.931. Conclusions: Atraumatic CCF has certain characteristic appearances on SPECT/CT. It should be enrolled in the differential diagnoses when costal cartilages of patients with malignant tumors show abnormal elevated 99mTc-MDP uptake on scintigraphy. Single-photon emission computed tomography/CT has excellent diagnostic power in detecting atraumatic CCF.